Male urinary incontinence treatment with AMS 800 artificial urinary sphincter - Černiauskienė, Aušra; Snicorius, Marius; Valatka, Paulius (Lietuvos chirurgija, 2017)
ObjectiveOur purpose is to review results of AMS 800 artificial urinary sphincter implantation for treatment of male stress urinary incontinence.To evaluate indications, contraindications, patient assessment, operative technique and complications of AMS 800 device.Materials and methodsWe used up to date literature of PubMed database.ResultsSuccess rates of artificial urinary sphincter AMS 800 vary between 61% and 100%. 80 – 90% of patients were satisfied with theoutcome and would recommend having the surgery. The complication rates are generally low and varies between 1–31%.AMS 800 5-year functioning without complications rates vary between 59% and 79%.ConclusionsAMS 800 artificial urinary sphincter is highly effective and time tested treatment of moderate and severe stress urinary incontinence.This device shows effective results and significantly improves the quality of life for appropriate selected patients.
Keywords: male urinary incontinence; artificial urinary sphincter; radical prostatectomy; AMS 800; review